Serologic Markers of Previous Malaria Exposure and Functional Antibodies Inhibiting Parasite Growth Are Associated With Parasite Kinetics Following a Plasmodium falciparum Controlled Human Infection. (12th August 2019) - Achan, Jane; Reuling, Isaie J; Yap, Xi Zen; Dabira, Edgard; Ahmad, Abdullahi; Cox, Momodou; Nwakanma, Davis; Tetteh, Kevin; Wu, Lindsey; Bastiaens, Guido J H; Abebe, Yonas; Manoj, Anita; et al.
Abstract: Background: We assessed the impact of exposure to Plasmodium falciparum on parasite kinetics, clinical symptoms, and functional immunity after controlled human malaria infection (CHMI) in 2 cohorts with different levels of previous malarial exposure. Methods: Nine adult males with high (sero-high) and 10 with low (sero-low) previous exposure received 3200 P. falciparum sporozoites (PfSPZ) of PfSPZ Challenge by direct venous inoculation and were followed for 35 days for parasitemia by thick blood smear (TBS) and quantitative polymerase chain reaction. Endpoints were time to parasitemia, adverse events, and immune responses. Results: Ten of 10 (100%) volunteers in the sero-low and 7 of 9 (77.8%) in the sero-high group developed parasitemia detected by TBS in the first 28 days (P = .125). The median time to parasitemia was significantly shorter in the sero-low group than the sero-high group (9 days [interquartile range IQR 7.5–11.0] vs 11.0 days [IQR 7.5–18.0], respectively; log-rank test, P = .005). Antibody recognition of sporozoites was significantly higher in the sero-high (median, 17.93 [IQR 12.95–24] arbitrary units [AU]) than the sero-low volunteers (median, 10.54 [IQR, 8.36–12.12] AU) (P = .006). Growth inhibitory activity was significantly higher in the sero-high (median, 21.8% [IQR, 8.15%–29.65%]) than in the sero-low group (median, 8.3% [IQR, 5.6%–10.23%]) (P = .025). Conclusions: CHMI was safe and well tolerated in this population. Individuals with serological evidence of higher malaria exposure were able to better control infection and had higher parasite growth inhibitory activity. Clinical Trials Registration: NCT03496454. Abstract : In this controlled human malaria infection study with Plasmodium falciparum sporozoite challenge, individuals with serological evidence of higher recent and cumulative malaria exposure had a longer prepatent period, lower mean parasite density at the time of treatment, and fewer symptoms of malaria.